Oscilações de nanoanéis e nanofitas de Möbius e empacotamento de cadeias carbônicas - Santos, Sérgio Gomes dos (2013)
Classical molecular dynamics techniques were employed to investigate three relevant problems for carbon-based nanosystems. First, we described the axial sliding of normal carbon nanorings (NCNs) and Möbius carbon nanorings (MCNs) along a single-walled carbon nanotube with hydrogen-terminated edges. C300H100 NCN and MCN nanostructures, along with armchair single-walled carbon nanotubes with chiralities (16,16), (18,18), and (20,20) were selected to perform molecular dynamics simulations using the Forcite program. The NCN:CNT systems exhibited an oscillatory movement with an initial frequency of about 10 gigahertz, decaying slowly with time, while the amplitude remained practically constant, except for the (16,16)-CNT. The MCN:CNT systems initially oscillated as the NCN:CNT, but a strong damping regime ensued, e_ectively stopping the oscillation after 400 ps for all MCN:CNT structures investigated. Second, the packing of polyacetylene (CnH2n+2) inside the C560 fullerene was simulated. With polyacetylene growth, two regimes were observed: the radius of gyration increases linearly with the number of carbon atoms in the chain, followed by a saturation regime that occurs when n = 200.